Preface - Stanimirović Predrag; Stupina Alena; Kovalev Igor; Mourtas Spyridon; Sahoo Jajati Keshari (ITM Web of Conferences)
The preface provides an overview of the III International Workshop “Hybrid Methods of Modeling and Optimization in Complex Systems” (HMMOCS-III 2024), held from December 2-4, 2024, in Krasnoyarsk, Russian Federation. The workshop brought together international experts to discuss advanced topics in mathematical modeling, optimization, and complex systems. The proceedings contain 50 selected papers reflecting the latest advancements in hybrid methods and interdisciplinary approaches to modeling and optimizing complex systems.